italiano (Società e diritti, 2020)
In a context in which the younger generations are increasingly at the mercy of disillusionment, nihilism, indifference, individualism, within a context increasingly characterized by the contrast with the other, rather than by collaboration and cooperation. This paper expose an empirical research about the theme “justice and human right” carried out by the IUSVE (Salesian University Institute of Venice), in network with the Universidade Católica de Brasilia (Brazil), Universidad Autonoma de Querétaro (Mexico) and Centro de Enseñanza Superior en Humanidades y Ciencias de la Educación " Don Bosco "(CES) (Spain), through the opinion of university student coming from four different countries.